2008
DOI: 10.1007/s11274-008-9814-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the efficiency of different extraction procedures on the anti microbial activity of selected medicinal plants

Abstract: Many doubts still persist even today when it comes to selection of the solvents for extracting the active constituents from various Indian medicinal plants. This study was aimed at assessing and establishing the best solvent for extracting the active constituents from 10 plant extracts. Thin layer chromatography (TLC) was used to separate and establish the active constituents present in each of the medicinal plants. Active constituents from each plant were extracted by using three different solvent systems nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…[14] To the best of the authors' knowledge and following a survey of the pertinent literature, only a few reports about the antibacterial activity of the essential oils and crude methanol extract of M. communis leaves have been published [15][16][17] , although several authors have found that the solvent used and the extraction system may modify the antibacterial activity of the extracts. [18] For these reasons, the aim of the work was to test the efficacy of various leaf and berry extracts against a diverse range of food-borne pathogens and food spoilage bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[14] To the best of the authors' knowledge and following a survey of the pertinent literature, only a few reports about the antibacterial activity of the essential oils and crude methanol extract of M. communis leaves have been published [15][16][17] , although several authors have found that the solvent used and the extraction system may modify the antibacterial activity of the extracts. [18] For these reasons, the aim of the work was to test the efficacy of various leaf and berry extracts against a diverse range of food-borne pathogens and food spoilage bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ethyl acetate is inexpensive, which is good from an economical viewpoint [ 41 ]. Chloroform is non-inflammable and is used for extraction of the active constituents from shrubs and other related plant species [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-polar organic solvent extractions such as hexane and petroleum ether extracts show very low antibacterial activity (6.47 to 10.64 mm) on Staphylococcus aureus (SA) and Bacillus cereus (BC). Muthuvelan and Raja (2008) suggested that the polarity distribution of antibacterial compounds in plants varies depending on species and plant families. Non-polar solvents may not be a good choice in extracting antibacterial metabolites in this case since most of the targeted metabolites are at the moderately polar end of the spectrum.…”
Section: Effect Of Different Extraction Solvents and Geographical Originmentioning
confidence: 99%